KERUSAKANKROMOSOM BAWANG MERAH (Allium cepaL.) AKIBAT PERENDAMAN DENGAN ETIDIUM BROMIDA - Fibayani Imaniar, Eka; Pharmawati, Made (SIMBIOSIS, 2014)
The aim of this research was to identify thedamage of onion’s( Alliumcepa L.) chromosomes causedbyethidiumbromide submersion for 6and12hoursat 500ppm. The methodused to study chromosome damage of onionroot tip wassquash technique. The result showed several types of chromosomedamagesuch as the formation of, micronuclei, nuclear buds and chromosome bridges. At 6 hours submersion,the average percentageof chromosomal damage was 2.99 %, while in submersion for 12 hours, the average percentage of chromosomal damage was 6.81 %. Keywords:Ethidium bromide, chromosome damage, Allium cepa L .